Pembimbingan Administrasi Portal Berita Persiapan Verifikasi Dewan Pers - Nani Harlinda Nurdin; Rulinawaty; Marini (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
In Indonesia online media, news portals are required to undergo a verification process by the Press Council. To be verified, the news portal media company is obliged to complete the requirements including; a) incorporated as a Limited Liability Company (PT); b) has a Taxpayer Identification Number (NPWP); c) has an editorial office; d) has an editorial structure; e) the editorial staff is led by a certified senior journalist; f) have employees; g) registered in labor insurance; h) attach proof of employee payroll sheet. This requirement is still followed by other requirements, as an indicator of the feasibility of a news portal company. The monitoring partner of the Matarakyat dotcom news portal, an online media under the banner of the people. News, is experiencing administrative problems in facing the verification of the Press Council. Lecturers of the State Administration Study Program, Faculty of Social and Political Sciences (FISIP), University of East Indonesia (UIT) Makassar, together with a team from the FHISIP of the Open University (UT), and the Faculty of Social and Political Sciences at the University of Bosowa (Unibos) Makassar, carry out Community Service (PKM) guidance. With the guidance method, the 15 employees and journalists obtained results that were believed to be able to overcome the problems at hand. The mentoring has succeeded in providing understanding, knowledge and application in the work practices of partners, before the start of factual verification by the Press Council.